2012
DOI: 10.1002/ird.1667
|View full text |Cite
|
Sign up to set email alerts
|

Construction Characteristics and Management Practices of In‐farm Irrigation Ponds in Intensive Agricultural Systems — Agronomic and Environmental Implications

Abstract: The structural and management characterization of 101 ponds, used for greenhouse drip irrigation, was assessed on the south‐eastern coast of Spain, with the objective of proposing more sustainable management practices. Different management methods were carried out by growers with the aim of controlling pond biological activity and improving the irrigation water quality. Pond covering was highly effective in preventing submerged aquatic vegetation (SAV) development but the high cost of installing and maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Regarding the type of construction, four types of ponds, grouped into two main categories, were represented ( Fig. Artificial-substratum ponds were above ground level, submitted to intensive management (periodic dredging and biocide treatments) and on average were 25 (CON) and 8 (PET) years old (Casas et al, 2011b;Juan et al, 2012). Natural-substratum ponds included embankments in small streams (EMB, n = 37) and ponds excavated in natural depressions (EXC, n = 18).…”
Section: Pond Selection and Characterisationmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the type of construction, four types of ponds, grouped into two main categories, were represented ( Fig. Artificial-substratum ponds were above ground level, submitted to intensive management (periodic dredging and biocide treatments) and on average were 25 (CON) and 8 (PET) years old (Casas et al, 2011b;Juan et al, 2012). Natural-substratum ponds included embankments in small streams (EMB, n = 37) and ponds excavated in natural depressions (EXC, n = 18).…”
Section: Pond Selection and Characterisationmentioning
confidence: 99%
“…Recent studies concluded that artificialsubstratum ponds in this region are subjected to aggressive management regimes compared to natural-substratum ponds, characterised by periodic dredging and biocide application, primarily copper sulphate (Casas et al, 2011b;Juan et al, 2012). Recent studies concluded that artificialsubstratum ponds in this region are subjected to aggressive management regimes compared to natural-substratum ponds, characterised by periodic dredging and biocide application, primarily copper sulphate (Casas et al, 2011b;Juan et al, 2012).…”
Section: Pond Typology and Diversitymentioning
confidence: 99%
See 3 more Smart Citations